Jumat Khutbah As Community Education Strategy For Family Stability Among Muslim Adults In Ibadan Metropolis, Nigeria - Ganiyu Adekola; AbdulRazaq, O. Kilani (Al-Fadlan: Journal of Islamic Education and Teaching, 2023)
Today, family instability (separation or a divorce) is predominant among Muslims in Ibadan metropolis. This is evidenced by the rate of separation and divorce cases, involving Muslim families in social welfare offices and customary courts in the city. The consequences of such family instability are among the indicators that placed Nigeria among 3rd World countries. Jumat Khutbah is usually used as community education tool to send messages of peace in the Muslim communities. It against this background that this research foresees the need to investigate how Jumat Khutbah as community education strategy responds to the contemporary problem of family instability among the Muslims in Ibadan metropolis. Two hypotheses and one research question guided the study. Qualitative and quantitative instruments were used to collect information from forty-five Imams, chairmen and secretaries of mosques and three hundred worshipers that were systematically selected while listening to khutbah in the fifteen purposively selected mosques in Ibadan metropolis. Data collected on the hypotheses were analysed with correlation while the research question was answered with content analysis of the information collected through the KII. The results revealed that a significant relationship exists between khutbah presentation and family stability and that a significant relationship exists between listening to and acceptance of khutbah messages and reduction of family instability. The study therefore recommends that Leadership of muslim communities should continuously motivate jumat Imams to ensure that issue of family stability and management of family instability enjoy more time allocation in jumat khutbah more regularly and that rather than going to conventional or sharia court on resolution of family disputes, active process of intervention, reconciliation and rehabilitation should be put in place as directed by Quran 4:35 to manage family issues among members of the muslim communities.